(untitled) (Proceedings of Southern Federal University. Philology, 2020)
M.A. Sholokhov (1905–1984) and V.F. Bokov (1914–2009) met in Rostov-on-Don in August 1964. A two-hour conversation took place at the initiative of the author of «And Quiet Flows the Don», who learned about the «literary ship» – traveling along the Don and performing in the villages and on farms with the reading of poems by young writers, headed by V.F. Bokov. Bokov wrote several poems about Sholokhov, the main of which – «Meeting with Sholokhov» (1964) – was to be included in his book of poems «On the Don», but, due to the arbitrariness of the editor, the publication is not included. In September 1964 Bokov sent it by letter to Sholokhov and read it «everywhere from the rostrum». The poet actively worked on this text, preparing a substantially updated version of it for his Collected works (1983–1984). One of the brightest details of Sholokhov’s image found by the poet is his naming through the naming of the famous Tolstoy estate: Rejoice, laugh and Hello, / our Yasnaya Polyana!. Another poem of this subject – «You remember me / Sholokhov called…» – V.F. Bokov included in a letter to the Don poet A.A. Ter-Markaryan. According to the image of the poet, Sholokhov, as it were, appointed Bokov as the «father» of the young writers accepted by him under his protection: Be your father to them, Victor. In the poem «The Old Cossack» the Sholokhov’s theme at the end, but, thus, becomes decisive. With the poet’s sense of humor, he writes that if this old Cossack would meet Sholokhov – there would be a novel! In his works on Sholokhov’s theme, Bokov proved himself, as in his work as a whole, a major master of the artistic word. Keywords: V.F. Bokov, M.A. Sholokhov, Don meeting, the image of the writer. DOI 10.18522/1995-0640-2020-1-12-20